MACROSCOPIC AND MICROSCOPIC INTERMESENTERIC COMMUNICATIONS - Kachlik, David; Baca, Vaclav (Biomedical papers, 2006)
The aim of this study was to describe all levels of the intermesenteric communications because of their importance in vascular diseases of the colon. The connections of superior and inferior mesenteric networks are very important in cases of acute or chronic obstruction to prevent ischemia and necrosis. Angiograms of mesenteric arteries were studied (40), cadaverous large intestine samples with mesentery and feeding vessels were dissected (36) or injected with India ink solution (24) or methylmetacrylate Mercox (41). In 7.9 % of cases an intermesenteric connection was described, named anastomosis intermesenterica accessoria and classified according to Pikkieff's1 proposal. The marginal artery in the left colic flexure forms an arch called Riolan's arcade2 or Haller's anastomosis3 and is present in 95 % of cases. Infrequent anastomosis between straight vessels and mighty plexuses in the intestinal wall were registered. There are no regional differences when compared to the rest of colon.
Keywords: Mesenteric/Intermesenteric/Anastomosis/Injection/Arterial/Microcirculation